Integralidad del sentido moral en la formación sacerdotal (2020)
This article presents results of research work entitled: "Moral training in the greater Seminary of Bogotá, a look from social representations, which purpose was to characterize social representations concerning the moral sense, who seminarists for training in the greater Seminary of Bogotá, have built which identified the aspects that characterize these representations through a descriptive and interpretive information analysis by the techniques of interview that allow establish them perspectives conceptual of who were interviewed, associated with the sense moral. In conclusion, the moral sense is born from interaction with society and that there are designated as appropriate behavioral standards, so that for the seminarians, practice occurs through the experiences in community, since is there where put into practice the concepts which are taught during the priestly formation and in general, during their training as individuals.